Fictionality in historical television series - Hajdu, Péter (Primerjalna književnost, 2020)
The most obvious formal feature of the historical novel as the genre founded by Walter Scott is the duplicity of a fictional foreground story and a historically approved background. Many television series have a historical past setting, and many of them can be seen as historical novels. The 2005-7 series Rome kept something of the Scottian structure of fictional foreground story. The Pullo and Vorenus story line is fictional, and it stages the life of ordinary people, while historical characters like Julius Caesar and Pompey or Antony and Augustus do not merely form a factual background. The fictional and non-fictional stories are in balance, and they together offer a vivid and convincing representation of the past. Many historical television shows use the past only as decorative setting for a story full of intrigue, violence and sex (The Tudors, The Borgias). These may be described as historical (anti)romances, which tend to focus exclusively on the elite. Another kind of historical novel has been developed by some shows that (as if at the other extreme) eliminate the historical facts even from the background and represent everyday life of ordinary people in its (semi-)historical otherness. In shows like Mad Men or The Knick, no event of political history is mentioned, no historical person appears in the background. However, these shows successfully represent the otherness of the past from the viewpoint of public discourse on issues of race, gender, or even morality, phenomena which can be regarded as the development of a new kind of historical novel encouraged by the twentieth-century ideals of historiography.
Keywords: anachronism; anahronizem; documentarity; dokumentarnost; fictionality; fikcijskost; historical novel; Mad Men; Oglaševalci; realism; realizem; Rim; Rome; television series; televizijske nadaljevanje; zgodovinski roman